Characteristics of suspected COVID-19 patients admitted with non-COVID illness in department of Endocrinology, BIRDEM General Hospital, Dhaka - Afsana, Faria; Parvez, Abdullah Al; Nahar, Jubaida; Islam, Mohammad Aminul; Hossain, Kazi Nazmul; Rouf, Rushda Sharmin Binte; Shefin, Sultana Marufa; Amin, Mohammad Feroz; Ashrafuzzaman, SM; Pathan, Md Faruque (BIRDEM Medical Journal, 2020)
Background: Since March 2019 the outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in Bangladesh. There is variable presentation of COVID-19. Though SARS-CoV-2 primarily involves respiratory system, as time passing on it is evident that it can affect any other system including gastrointestinal, cardiovascular and neurological system. This study described the characteristics of the patients admitted in Department of Endocrinology, BIRDEM General Hospital with non-COVID illness and later revealed positive for SARS-CoV-2. Methods: This observational study was conducted during the period of 13th April to 14thOctober, 2020.Data of all patients admitted in Department of Endocrinology, BIRDEM General Hospital during this period was retractedretrospectively from hospital electronic medical records with prior permission from institutional head. Though admitted for non-COVID illness, patientshavingsymptoms or supportive lab investigations of COVID- 19 were advised RT-PCR for SARS-CoV-2. All hospital records of these suspected COVID-19 cases wererecoded and analyzed by SPSS version 20. Results:Total patients were 63. Among them 21(33.3%) patients were admitted with uncontrolled diabetes (DM),19(30.2%) had other endocrinopathies(later query revealed history of fever),8(9.5%) had newly detected DM,11(7.5%)had hypoglycemia,6(9.6%) had general weakness. Though all study subjects were advised to do RT-PCR for COVID, 22(34.9%) refused the test either due to symptom denial or due to cost of the test and 24(38.1%) become positive. Conclusion: Non-critically ill COVID-19 patients had variable clinical characteristics. This study shows that uncontrolled diabetes mellitus, newly detected diabetes and hypoglycemia are found in patients with COVID- 19 and may not have typical clinical features. Birdem Med J 2020; 10, COVID Supplement: 29-32